Legal Vacancies Regarding Notarial Deeds Made In Foreign Languages Without Official Translation And Their Implications for The Validity Of The Deed - Hartati, Titin; Redi, Ahmad (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
In accordance with Article 43 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (UUJN), this study investigates the legal gaps pertaining to the drafting of notarial deeds in foreign languages without an official translation. This phenomenon often occurs in transactions involving foreign parties or cross-border transactions. Although the UUJN stipulates that deeds must be prepared in Indonesian and, if the parties do not understand Indonesian, an official translation must be provided, there are no detailed regulations regarding the legal consequences if this provision is ignored. As a result, legal uncertainty arises that has the potential to reduce the validity of the deed from an authentic deed to a private deed, even triggering the cancellation of the deed in a dispute. This study outlines the existing regulations, identifies the legal gaps, and analyzes their implications from the perspectives of civil law, administrative law, protection of foreign parties, and legal risks for notaries. Several case studies and court decisions indicate differing interpretations regarding the validity of foreign-language deeds without an official translation, indicating the need for clear technical guidelines. Recommendations include revising the UUJN or issuing implementing regulations by the Ministry of Law and Human Rights, as well as implementing the precautionary principle by notaries through sworn translators to ensure legal protection and certainty for the parties. The results are expected to provide an academic basis for policymakers in strengthening regulations governing the language used in notarial deeds.